Fermentasi Silase dan Manfaat Probiotik Silase bagi Ruminansia - Y Widyastuti (Faculty of Animal Science, Bogor Agricultural University, 2008)
Forage conservation has long been a part of the agricultural scene in some countries in the world. Ensilage is a preservation method for moist forages that is based on natural lactic acid fermentation under anaerobic conditions. There are six phases which occur during ensilage, storage and feed-out of the fermented forages. The technology of silage making is not popular in Indonesia, although ensilage may successfully occurs in tropical area including Indonesia. The reason may be due to limited information available regarding ensilage for the farmers. This review covered silage fermentation process and probiotics effect of feeding silage to the ruminants. The role of lactic acid bacteria is very important both from the preservation and antimicrobial points of view. Key words: lactic acid bacteria, fermentation, silage, probiotics